Theoretical approaches to the synthesis of discrete signals with necessary properties - Gorbenko, I.D.; Zamula, A.A. (Radiotekhnika, 2021)
Methods for information exchange, formation and processing of data used in information and communication systems (ICS), as well as classes of broadband signals used as a physical data carrier, do not provide the necessary (for individual ICS applications) indicators of cyber and information security, noise immunity of reception signals and secrecy of IKS functioning. Most of the existing systems use signals, the construction of which is based on linear laws, which allows an attacker, based on the establishment of the parameters of the signals used in the system, to carry out deliberate interference in the operation of the ICS with minimal energy consumption. The article presents conceptual approaches to the construction of secure ICS, which determine the need to cover the entire spectrum of information transformations in the complex, and based on the synthesis of signal systems with improved ensemble, correlation, structural properties. A method is proposed for synthesizing discrete derivatives of signals based on nonlinear discrete complex cryptographic signals (CS) and orthogonal signals formed on the basis of the rows of the Hadamard matrix (initial signals),. Based on computer modeling and the performed calculations, it is shown that the derivative signals formed on the basis of cryptographic sequences and rows of the Hadamard matrix have improved properties compared to orthogonal and linear classes of signals. Approaches to the construction are stated and a general characteristic of the hardware-software complex for synthesis, analysis, study of properties, generation, processing of a number of studied signal classes is given. It is shown that the use of such signals will improve such indicators of the system functioning as information security, noise immunity of signal reception and secrecy of functioning.